Early Fiber Number Ratio Is a Surrogate of Corticospinal Tract Integrity and Predicts Motor Recovery After Stroke. Issue 4 (April 2016) - Bigourdan, Antoine; Munsch, Fanny; Coupé, Pierrick; Guttmann, Charles R.G.; Sagnier, Sharmila; Renou, Pauline; Debruxelles, Sabrina; Poli, Mathilde; Dousset, Vincent; Sibon, Igor; Tourdias, Thomas
Abstract : Background and Purpose—: The contribution of imaging metrics to predict poststroke motor recovery needs to be clarified. We tested the added value of early diffusion tensor imaging (DTI) of the corticospinal tract toward predicting long-term motor recovery. Methods—: One hundred seventeen patients were prospectively assessed at 24 to 72 hours and 1 year after ischemic stroke with diffusion tensor imaging and motor scores (Fugl-Meyer). The initial fiber number ratio (iFNr) and final fiber number ratio were computed as the number of streamlines along the affected corticospinal tract normalized to the unaffected side and were compared with each other. The prediction of motor recovery (ΔFugl-Meyer) was first modeled using initial Fugl-Meyer and iFNr. Multivariate ordinal logistic regression models were also used to study the association of iFNr, initial Fugl-Meyer, age, and stroke volume with Fugl-Meyer at 1 year. Results—: The iFNr correlated with the final fiber number ratio at 1 year ( r =0.70; P <0.0001). The initial Fugl-Meyer strongly predicted motor recovery (≈73% of initial impairment) for all patients except those with initial severe stroke (Fugl-Meyer<50). For these severe patients (n=26), initial Fugl-Meyer was not correlated with motor recovery ( R 2 =0.13; p=ns), whereas iFNr showed strong correlation ( R 2 =0.56; P <0.0001). In multivariate analysis, the iFNr was an independent predictor of motor outcome (β=2.601; 95% confidence interval=0.304–5.110; P =0.031), improving prediction compared with using only initial Fugl-Meyer, age, and stroke volume ( P =0.026). Conclusions—: Early measurement of FNr at 24 to 72 hours poststroke is a surrogate marker of corticospinal tract integrity and provides independent prediction of motor outcome at 1 year especially for patients with severe initial impairment. Abstract : Supplemental Digital Content is available in the text.